Strategi Koping Pada Mahasiswa Yang Bermain Game Online - Pitasari, Melita Nur; Estria, Suci Ratna (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Background: Online gaming has become a necessity for many teenagers to divert most of their time into playing online games. One of the negative effects of the diversion affects the coping strategies used by someone who plays online games in dealing with problems. Objective: To find out the coping strategy is for students who play online games at the Faculty of Health and Science of Universitas Muhammadiyah Purwokerto. Method: This is a quantitative research using descriptive analysis method. The population is 80 students who use online games at the Faculty of Health and Science of Universitas Muhammadiyah Purwokerto. Total sampling technique is used as the sampling method with a sample size of 80. The univariate analysis is used to analyze the data. Results: Respondents are mostly 19 years old on average. There are 43 female respondents and 37 male respondents. Based on the frequency of playing online games, there are 43 students with low category, 24 students in medium category, 12 students in high category, and one student in very high category. Based on the data of coping strategies used by respondents, there are 71 students using the type of problem-focused coping strategies and 9 students using the type of Emotion-focused coping strategies. Conclusion: There are 71 students using the type of problem-focused coping strategies and 9 students using the type of Emotion-focused coping strategies.Keywords: coping strategies, playing online games